Resistivity Imaging: Application of 2D Resistivity Survey for Under Groundwater Prospecting in New Campus of Sulaimani University and Surrounding areas, Sulaimani City, NE Iraq - Othman, Halo Abdullah (Sulaimani Journal for Pure and Applied Sciences, 2019)
Groundwater, the hidden source of life, it is so important to be estimated quantitatively and qualitatively before extracting and using. New campus of university of Sulaimani locates at the west of the city, has a vast area, so that it needs to more water supplies for daily uses and irrigation. Therefore, conducting of geophysical survey was decided to ensure the existence of underground water then drilling water wells. Next, a 2D electrical tomography was carried out along seven profiles of 720m using Syscal instrument with its accessories in and out of the university. After that, the obtained data were processed then interpreted using Res2Dinv software to approach a final conclusion. Finally, the results showed in profiles 1, 2, and 3, the resistivity value was about 5-157 ohm.m and about 20-30 ohm.m in the water bearing layer with nearly 20m depth, deep well of depths ranging from 100 to 125 are recommend near the location of electrode are indicated on the resistivity sections, the expected productivity is moderate to low. At profile 4, resistivity of 2-300ohm.m was obtained and 20-100ohm.m in the water bearing layer of more than 20m depth, deep well is not recommended, the expected productivity is low. In geophysical point of view, the surveyed locations beneath the profiles 5 and 6 not suitable for drilling an artesian well, a Marley limestone of low resistivity 9-40ohm.m was detected extending 70-150m of depth . Also, profile 7, is not suitable for drilling water well because of clay layers of low resistivity ranging 18-30ohm.m in depth of 30m.
Keywords: Electrical Resistivity; Groundwater,2D resistivity survey